Find me [compact disc, unabridged] : a novel - Burke, Alafair (Burke, Alafair. Ellie Hatcher series., 2022)
Hope Miller suffers from amnesia and seeks a fresh beginning. When her best friend Lindsay Kelly discovers Hope has vanished, the only lead is a drop of blood that connects to a notorious murderer out of Kansas. With nowhere else to turn, Lindsay calls NYPD homicide detective Ellie Hatcher, the daughter of the cop who dedicated his life to hunting the Kansas killer.